A Contiguous 66-kb Barley DNA Sequence Provides Evidence for Reversible Genome Expansion - Shirasu, Ken; Schulman, Alan H.; Lahaye, Thomas; Schulze-Lefert, Paul

(untitled) (Genome Research, 2000)
Organisms with large genomes contain vast amounts of repetitive DNA sequences, much of which is composed of retrotransposons. Amplification of retrotransposons has been postulated to be a major mechanism increasing genome size and leading to “genomic obesity.” To gain insights into the relation between retrotransposons and genome expansion in a large genome, we have studied a 66-kb contiguous sequence at the Rar1 locus of barley in detail. Three genes were identified in the 66-kb contig, clustered within an interval of 18 kb. Inspection of sequences flanking the gene space unveiled four novel retroelements, designated Nikita, Sukkula,Sabrina, and BAGY-2 and several units of the knownBARE-1 element. The retroelements identified are responsible for at least 15 integration events, predominantly arranged as multiple nested insertions. Strikingly, most of the retroelements exist as solo LTRs (Long Terminal Repeats), indicating that unequal crossing over and/or intrachromosomal recombination between LTRs is a common feature in barley. Our data suggest that intraelement recombination events deleted most of the original retrotransposon sequences, thereby providing a possible mechanism to counteract retroelement-driven genome expansion.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF254799.]